2019
DOI: 10.1007/s12576-019-00692-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of astaxanthin supplementation and electrical stimulation on muscle atrophy and decreased oxidative capacity in soleus muscle during hindlimb unloading in rats

Abstract: The effects of a combination of the antioxidant astaxanthin (AX) and electrical stimulation (ES) on muscle mass and mitochondrial oxidative capacity were investigated in the soleus muscle of hindlimb unloaded rats. Five groups of male Sprague-Dawley rats were used; control, 1-week hindlimb unloading (HU), HU + AX, HU + ES, and HU + AX + ES. Respective rats in the AX groups received 50-mg/kg AX twice daily during HU. Calf muscles of rats in the ES groups were electrically stimulated for 240 s/day during HU. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 53 publications
5
22
1
1
Order By: Relevance
“…It should be noted that the observed effect sizes-increase in tetanic force and reduction in mitochondrial calcium accumulation following repetitive stimulation-were modest. This however is consistent with former measurements using either other antioxidants or AX to improve muscle function or to modify body metabolism by AX [54][55][56].…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that the observed effect sizes-increase in tetanic force and reduction in mitochondrial calcium accumulation following repetitive stimulation-were modest. This however is consistent with former measurements using either other antioxidants or AX to improve muscle function or to modify body metabolism by AX [54][55][56].…”
Section: Discussionsupporting
confidence: 91%
“…Using an exercised mouse model, Liu et al (63) suggested that astaxanthin accelerated lipid utilization in skeletal muscle and reduced intermuscular pH during aerobic exercise through elevation of PGC-1α. Studies conducted by Kanazashi et al (31,32) identified a similar pattern to astaxanthin alone, astaxanthin with intermittent loading and astaxanthin with electrical stimulation retained mitochondrial biogenesis by raising PGC-1α and eNOS expression in the soleus muscle of hindlimb unloaded mice. The total 5'-adenosine monophosphate-activated protein kinase (AMPK) content in skeletal muscle was also significantly augmented in the exercised animals fed with astaxanthin from H. pluvialis than the control group.…”
Section: The Mechanism Of Action Of Astaxanthinmentioning
confidence: 74%
“…The data from this study showed that increases in 4-hydroxy-2-nonenal (4-HNE)-modified protein, 8-hydroxy-2'-deoxyguanosine (8-OHdG), plasma CK activity and myeloperoxidase (MPO) activity in the gastrocnemius and heart caused by exercise were attenuated by astaxanthin (52). Astaxanthin treatment was effective in lowering the concentrations of malondialdehyde (MDA) or TBARS, ROS and carbonylated protein in various animal models (28)(29)(30)(31)(32)38,39,41,53).…”
Section: The Mechanism Of Action Of Astaxanthinmentioning
confidence: 85%
See 2 more Smart Citations